IMPROVING STUDENTS’ LISTENING COMPREHENSION ON FAIRY TALE THROUGH DICTOGLOSS TECHNIQUE - Saputri, Kartika Ardhia; Apriliaswati, Rahayu; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to investigate how Dictogloss improved students? listening comprehension on fairy tale at tenth grade students of SMA Islamiyah Pontianak in academic year 2017/2018. The research was Classroom Action Research. The research subject was tenth grade students in class XA. The writer used field note, observation checklist, and listening test as tools of collecting data. The data analysis showed the students? listening comprehension in discriminating sound of past tense action verbs improved through preparation stage of Dictogloss. The students? listening comprehension in finding specific information of fairy tale improved through dictation stage of Dictogloss. In addition, the students? listening comprehension in finding main idea improved through reconstruction stage of Dictogloss. The students? concentration in listening comprehension of fairy tale were improved through reconstruction stage of Dictogloss. Dictogloss could improve students? listening comprehension and concentration in discriminating sound of past tense action verbs, finding specific information and main idea of fairy tale. Keywords: Fairy Tale, Dictogloss, Listening Comprehension.